Cognitive effects of brief and ultrabrief pulse bitemporal electroconvulsive therapy: a randomised controlled proof-of-concept trial. Issue 7 (2nd May 2020) - Martin, Donel; Katalinic, Natalie; Hadzi-Pavlovic, Dusan; Ingram, Anna; Ingram, Nicholas; Simpson, Brett; McGoldrick, Jenny; Dowling, Nathan; Loo, Colleen
Abstract: Background: Reduction of the pulse width has been reported to improve ECT outcomes with unilateral ECT (similar efficacy, fewer cognitive side effects), but has been minimally studied for bitemporal ECT. The only study comparing brief and ultrabrief pulse bitemporal ECT found reduced efficacy for bitemporal ultrabrief compared to bitemporal brief pulse stimulation. This randomised controlled trial (RCT) aimed to test if ultrabrief pulse bitemporal ECT results in fewer cognitive side effects than brief pulse bitemporal ECT, when given at doses adjusted with the aim of achieving comparable efficacy. Methods: Thirty-six participants were randomly assigned to receive ultrabrief (at 3 times seizure threshold) or brief (at 1.5 times seizure threshold) pulse bitemporal ECT given 3 times a week in a double-blind, controlled proof-of-concept trial. Blinded raters assessed mood and cognitive functioning over the ECT course. Results: Efficacy and cognitive outcomes did not differ significantly between the two treatment groups over the ECT course. The ultrabrief pulse group performed better on a test of visual memory assessed acutely after an ECT treatment. Conclusions: This study suggests there may be a small cognitive advantage in giving bitemporal ECT with an ultrabrief pulse when dosage is increased to match the efficacy of brief pulse bitemporal ECT, but the study was underpowered to fully examine this issue. Clinical Trials Registration: www.clinicaltrials.gov, NCT00870805.